2013
DOI: 10.1111/jvh.12098
|View full text |Cite
|
Sign up to set email alerts
|

Rare occurrence of occult hepatitis C virus in apparently uninfected injecting drug users: a two‐centre, masked, case–control study

Abstract: Occult hepatitis C virus (HCV) is a phenomenon where serum HCV RNA is not detected by sensitive commercial assays, but viral RNA is detected by ultrasensitive techniques. Occult HCV infection has not previously been studied in highly exposed, but apparently uninfected (EU) individuals. Two studies examining occult infection in EU subjects were undertaken - an initial two-centre, masked, case-control study based on cross-sectional samples (n = 35 subjects) and a single-centre confirmatory study based on longitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 8 publications
0
3
0
1
Order By: Relevance
“…These data strongly suggest that occult HCV infection may be present in at least some individuals who either spontaneously or after antiviral treatment have “cleared” virus from their serum [ 54 56 ].…”
Section: Hcv Oci Experiencementioning
confidence: 99%
See 1 more Smart Citation
“…These data strongly suggest that occult HCV infection may be present in at least some individuals who either spontaneously or after antiviral treatment have “cleared” virus from their serum [ 54 56 ].…”
Section: Hcv Oci Experiencementioning
confidence: 99%
“…It has been suggested that clearance of identifiable HCV from liver tissue and/or PBMC utilizing highly sensitive reverse transcription and nested polymerase chain reaction assays may be a better indicator of a long-term sustained response than the absence of HCV-RNA in serum or plasma [ 56 , 115 – 117 , 124 , 125 ]. Although the relevance of HCV-RNA detection in PBMCs alone, or in the liver in the absence of serum positivity, as well as other tissues is currently poorly understood, the ability of HCV to replicate in these extra hepatic cells, raises questions about the potential transmission risk to the liver from these sites and to other individuals as a result of blood exposure [ 123 , 126 – 129 ].…”
Section: Clinical Relevancementioning
confidence: 99%
“…Indeed, a recurrence of occult previous chronic hepatitis C with a persistently undetectable viraemia (and also persistently normal liver enzymes) that became detectable8 9 in the context of the leptospirosis is another possible explanation.…”
Section: Discussionmentioning
confidence: 99%
“…Тем не менее такая форма инфекции в ряде случаев приводит к фиброзу печени, циррозу и гепатоцеллюлярной карциноме [8]. Согласно многочисленным данным литературы, эта инфекция была обнаружена в различных группах пациентов, в том числе у 10-74% лиц с хроническими заболеваниями печени, криптогенным циррозом и гепатоцеллюлярной карциномой неясной этиологии [6,7,9,10], у больных, получающих регулярную заместительную почечную терапию в 3,7-26,5% случаев [5,6,11], у 0,5% реципиентов почечного трансплантата [6], у 10-20% потребителей инъекционных наркотиков [12], у 1,9-20% пациентов с заболеваниями системы крови [13][14][15][16]. Однако данные литературы, посвящённой обнаружению скрытой ВГС-инфекции при различных нозологических формах заболеваний системы крови, противоречивы [13][14][15][16].…”
Section: Introductionunclassified